ANALYSIS OF THE IMPACT OF CUSTOMER SATISFACTION IN THE RELATIONSHIP BETWEEN SERVICE ORIENTATION AND SERVICE QUALITY ON CUSTOMER LOYALTY OF MUSLIMAH SALON - Ibnu Jauzi; Ari Prasetyo (Universitas Airlangga, 2021)
ABSTRAKLoyalitas pelanggan merupakan hal yang harus diutamakan perusahaan jasa dalam menjalankan bisnisnya. Tanpa adanya pelanggan yang loyal terhadap perusahaan maka sustainbility perusahaan tersebut akan terancam. Penelitian ini bertujuan untuk meneliti dampak orientasi pelayanan dan kualitas pelayanan terhadap loyalitas pelanggan melalui kepuasan pelanggan pada salon muslimah di Kota Kediri. Apakah dalam mencapai loyalitas pelanggan harus melalui kepuasan pelanggan atau tidak. Penelitian ini menggunakan pendekatan kuantitatif dengan metode SEM PLS. Pengujiannya dilakukan menggunakan aplikasi SmartPLS 3.0 dengan kategori responden yaitu pelanggan yang telah merasakan produk salon muslimah di Kota Kediri. Hasil penelitian menunjukkan adanya efek moderasi kepuasan pelanggan dalam hubungan orientasi dan kualitas pelayanan terhadap loyalitas pelanggan.Hal tersebut mengindikasikan bahwa orientasi dan kualitas pelayanan yang dilakukan oleh salon muslimah di Kota Kediri bisa dikategorikan baik sehingga membuat para pelanggannya menjadi loyal.Kata Kunci: Loyalitas Pelanggan, Orientasi Pelayanan, Kualitas Pelayanan, Kepuasan Pelanggan, Salon Muslimah. ABSTRACTCustomer loyalty is something that must be prioritized by service companies in running their business. Without customers who are loyal to the company, the company's sustainability will be threatened. This study aims to examine the impact of service orientation and service quality on customer loyalty through customer satisfaction at Muslimah salons in Kediri. Whether to achieve customer loyalty must go through customer satisfaction or not. This study uses a quantitative approach with the SEM PLS method. The test was carried out using the SmartPLS 3.0 application with the respondent category, namely customers who have experienced Muslim salon products in Kediri. The results showed that there was a moderating effect of customer satisfaction in the relationship between orientation and service quality on customer loyalty. This indicates that the orientation and quality of service carried out by muslimah salons in Kediri City can be categorized as good so that it makes its customers loyal.Keywords: Customer Loyalty, Service Orientation, Service Quality, Customer Satisfaction, Muslimah Salon.DAFTAR PUSTAKACanalejo, A. M. C., & del Rio, J. A. J. (2018). Quality, satisfaction and loyalty indices. Journal of Place Management and Development, 11(4), 428-446. https://doi.org/10.1108/JPMD-05-2017-0040Ferreira, F. A. F., Jalali, M. S., Kavaliauskiene L. M., & Viana, B. A. C. P. (2015). A metacognitive decision making based-framework for bank customer loyalty measurement and management. Technological and Economic Development of Economy, 21(2), 280–300. https://doi.org/10.3846/20294913.2014.981764Giovanis, A., Athanasopoulou, P., & Tsoukatos, E. (2015). The role of service fairness in the service quality – relationship quality – customer loyalty chain. Journal of Service Theory and Practice, 25(6), 744-776. https://doi.org/10.1108/JSTP-11-2013-0263Kandampully, J., Zhang, T. C., & Bilgihan, A. (2015). Customer loyalty: A review and future directions with a special focus on the hospitality industry. International Journal of Contemporary Hospitality Management, 27(3), 379–414. https://doi.org/10.1108/IJCHM-03-2014-0151Makanyeza, C., & Chikazhe, L. (2017). Mediators of the relationship between service quality and customer loyalty. International Journal of Bank Marketing, 35(3), 540–556. https://doi.org/10.1108/IJBM-11-2016-0164Mandung, F., Modding, B., Hasan, S., & Ella, H. (2018). Effect of market orientation, service quality and service orientation on semen tonasa customer satisfaction and loyalty in Makassar city. International Journal Of Scientific & Technology Research, 7(12), 144-153.Mathe, K., Halsell, S. S., & Roseman, M. (2016). The role of customer orientation in the relationship between manager communications and customer satisfaction. Journal of Hospitality & Tourism Research, 40(2), 198–209. https://doi.org/10.1177%2F1096348013496278Pattanayak, D., Koilakuntla, M., & Punyatoya, P. (2017). Investigating the influence of TQM, service quality and market orientation on customer satisfaction and loyalty in the Indian banking sector. International Journal of Quality & Reliability Management, 34(3), 362–377. https://doi.org/10.1108/IJQRM-04-2015-0057Rajeswari, S., Srinivasulu, Y., & Thiyagarajan, S. (2017). Relationship among service quality, customer satisfaction and customer loyalty: With special reference to wireline telecom sector (DSL Service). Global Business Review, 18(4), 1041–1058. https://doi.org/10.1177%2F0972150917692405Ratnasari, R.T., Rusmita, S. A., Gunawan, S., & Prasetyo, A. (2019). Halal food certification to improve the competitiveness of east and middle business in Indonesia. 2nd International Conference on Islamic economics, Business and Philantropy, 1044-1056. Surabaya: KnE Social Sciences.Solimun, & Fernandes, A., A., R. (2018). The mediation effect of customer satisfaction in the relationship between service quality, service orientation, and marketing mix strategy to customer loyalty. Journal of Management Development, 37(1), 76-87. https://doi.org/10.1108/JMD-12-2016-0315Sugiyono. (2009). Metode penelitian bisnis. Bandung: CV. Alfabeta.Zameer, H., Tara, A., Kausar, U, & Mohsin, A. (2015). Impact of service quality, corporate image and customer satisfaction towards customers’ perceived value in the banking sector in Pakistan. International Journal of Bank Marketing, 33(4), 442–456. https://doi.org/10.1108/IJBM-01-2014-0015